Seminal plasma oxytocin and oxidative stress levels in infertile men with varicocele. (19th February 2014) - Mostafa, T.; Rashed, L. A.; Osman, I.; Marawan, M.
Summary This study aimed to assess seminal plasma oxytocin (OT) and oxidative stress (OS) levels in infertile men with varicocele (Vx). A total of 131 men were divided into fertile men (n = 20), fertile men with Vx (n = 17), infertile men without Vx (n = 40) and infertile men with Vx (n = 54). OT, malondialdehyde (MDA) and glutathione peroxidase (GPx) were estimated in seminal plasma. Mean levels of seminal OT, MDA were significantly decreased, and the mean level of GPx was significantly increased in fertile men with/without Vx compared with infertile men with/without Vx. Mean levels of OT, MDA were increased, and mean level of GPx was significantly decreased in Vx grade III cases compared with Vx grades I, II cases and in bilateral Vx cases compared with unilateral Vx. There was significant negative correlation between seminal OT with sperm count, sperm motility, seminal GPx and significant positive correlation with sperm abnormal forms, seminal MDA. It is concluded that seminal OT is significantly decreased in fertile men with/without Vx compared with infertile men with/without Vx. Seminal OT demonstrated significant negative correlation with sperm count, sperm motility, seminal GPx and significant positive correlation with sperm abnormal forms, seminal MDA. Seminal OT is associated with Vx grade and its bilaterality.